Study on the novel capacitive moisture sensing behaviour of nickel chromite nanoparticle based thick film. (15th October 2020) - Mondal, Partha Pratim; Mahapatra, Preeti Lata; Das, Sagnik; Saha, Debdulal
Graphical abstract: Highlights: Nickel chromite (NiCr2 O4 ) nanoparticles synthesis by a facile sol-gel method. Micro porous NiCr2 O4 thick film bulk production by tape casting process. Sensors delineate excellent humidity detection capability in the range 5–95%RH having fast response and recovery times. Sensors can be re-calibrated and reused by washing with non-aqueous solvent. Abstract: In this work, the novel and appreciable humidity sensing properties of microporous, spinel nickel chromite thick films are reported for the first time. NiCr2 O4 microporous, thick film prepared by tape casting of sol-gel derived nanopowder followed by sintering was sandwiched between two parallel silver electrodes to develop capacitive humidity sensor. Condensation in the surface pores and physisorption on the sensor surface are found to be responsible for the humidity sensing properties. The sensor shows excellent humidity sensing properties in the range of 5% to 95% RH (relative humidity) with a resolution of ~3 pF/%RH in the lower humidity range (5%−30% RH) at 1 kHz external electric field. The sensor also exhibited excellent repeatability (at least 50 cycles of 5%–95%RH), good stability of at least 6 months, and low hysteresis loss. The thick film sensors were characterized by XRD, FT-IR, FESEM, TEM, EDX, and contact angle measurement.